Learning Assessment, Measurement or Verification in the Classroom: A Case Study - José Pereira-Chaves (Revista Electrónica Educare)
The analysis of various evaluation processes that are developed in the classroom is essential to reinterpret the educational work and the learning achievements, based on the need of the teachers in offering the students a less repressive and more motivating alternatives to measure the study contents. Thus, the purpose of this research was to identify the type of relationship existing between the way it is taught and how it is evaluated -with the level of learning achievement of biological concepts in the classroom. For it, an ethnography was developed through a case study whose data collection techniques were: observations, interviews and a focus group. The findings confirmed that the evaluation was part of the summative proposal suggested by the Ministry of Public Education (MEP, for its name in Spanish). The teacher always applied a comprehensive evaluation, including different ways to verify contents, as well as the implementation of several skills by the students. Additionally, the teacher considered all the teaching strategies used, which generated motivation and concentration for each of the activities. Therefore, the strategies and teaching techniques went hand in hand with the learning evaluation.